A Multi-Agent Control Architecture for a Rescue Robot - Haber, Adam (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
Cognitive architectures investigate the components and interactions neccessary for construction of an intelligent system. Despite much progress and theory, implementations of architectures are rare. This research presents a novel cognitive architecture grounded in the design of a control system for an autonomous rescue robot. Experiments are conducted in high-fidelity 3D simulation of a rescue environment based on NISTs RoboCup Rescue.